Forms and correlates of child maltreatment among autistic children involved in child protection services - Jacinthe Dion; Jacinthe Dion; Geneviève Paquette; Geneviève Paquette; Mireille De La Sablonnière-Griffin; Mireille De La Sablonnière-Griffin; Malena Argumedes; Alexa Martin-Storey; Alexa Martin-Storey; Marie-Louise Bolduc; Sonia Hélie; Ève-Line Bussières (Frontiers in Child and Adolescent Psychiatry)
BackgroundChild maltreatment is a significant social problem impacting both health and society, with severe and enduring consequences. Certain children, such as those with neurodevelopmental conditions like autism, may be more at risk of experiencing maltreatment. However, little research has examined the characteristics of these children. This study aimed to compare child maltreatment and child protection services experienced by autistic children to those of non-autistic children.MethodDrawing from a representative selection of verified cases of child abuse investigated by child protection services in Quebec, Canada, a sample of 1,805 substantiated child maltreatment cases were analyzed.ResultsOverall, 4.0% (n = 73) of children had child protection services-reported autism diagnoses. Attention-deficit (OR = 2.207) and attachment problems risk (OR = 2.899) were higher among autistic children compared to non-autistic children. They were more likely to be boys (OR = 5.747), and to present with an intellectual disability (OR = 11.987), but less likely to have previously been investigated by child protection services (OR = 0.722).ConclusionThese findings suggest that autistic children who have been maltreated are facing specific challenges that require protective interventions tailored to their specific needs.